2005
DOI: 10.1108/09596110510620636
|View full text |Cite
|
Sign up to set email alerts
|

How to increase menu prices without alienating your customers

Abstract: Purpose -This paper analyzes the impact of menu descriptions on the selection of menu items. Furthermore, this paper examines the relationship between menu descriptions and the perceived value of the item. Design/methodology/approach -This study uses the different components of prospect theory (e.g. anchoring effects and framing effects). An experimental research design using mock menus was used to investigate the impact of item presentation, item selections, and menu descriptions on consumer judgments of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…A study conducted by Jang and Kim () found that providing both descriptive information and pictures can reduce the risk perception of neophobic consumers. Another study demonstrated that detailed information about the product can positively affect customers' value perception (Shoemaker et al ). Therefore, when displaying information about edible insect‐based food or products, it is critical to include nutritional and product development (cooking) process information, together with a picture of the product.…”
Section: Challenges For the Industrymentioning
confidence: 99%
“…A study conducted by Jang and Kim () found that providing both descriptive information and pictures can reduce the risk perception of neophobic consumers. Another study demonstrated that detailed information about the product can positively affect customers' value perception (Shoemaker et al ). Therefore, when displaying information about edible insect‐based food or products, it is critical to include nutritional and product development (cooking) process information, together with a picture of the product.…”
Section: Challenges For the Industrymentioning
confidence: 99%
“…In restaurants, menus may affect luxury perceptions, service knowledge, and choices (Beardsworth and Keil, 1997;Shoemaker et al, 2005;Yang et al, 2009). The use of extensive, descriptive menu labels is rather common in the hospitality industry (Wansink et al, 2001).…”
Section: Symbolic Price Cuesmentioning
confidence: 97%
“…However, while quality may be an important differentiating factor, customers in Nairobi may want to choose a restaurant on the basis of both satisfaction and value. Shoemaker et al (2005) defined value as the price charged, while Zeithmal (1988) [30]defined values as the products quality reflecting the price paid. She further observed that consumers use extrinsic cues, such as price, in forming perceptions of value.…”
Section: Introductionmentioning
confidence: 99%
“…She further observed that consumers use extrinsic cues, such as price, in forming perceptions of value. Shoemaker et al (2005) [26] adds that, if the price is too high relative to the other cues, then consumers will have poor perceptions of value and will have a decreased probability of purchase. Therefore value is the result of quality and price charged.…”
Section: Introductionmentioning
confidence: 99%